Studying epidemiology of stomatologic diseases of the children's population of republic Northern-Osetia Alania - D K Lianova; S A Avdolan; V M Slonova; A G Gontarev; F Yu Daurova (RUDN Journal of Medicine, 2008)
With change of economic model of the state rendering of the stomatologic help to the children's population has not ceased to be an actual problem, but, on the contrary, has received an even greater acutenessand importance. In the specified aspect development of the modern, economically proved approaches to problems of the organization of the stomatologic help is required to the children's population and introduction of itsher new models.